Reproductive Status and Net Replacement Rate Brahman Cross in Livestock Production Cooperative Maju Sejahtera Tanjung Sari District South Lampung Regency - Sri Suharyati; Dani Al Fajri; Sulastri Sulastri (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
The purpose of this study was to determine the reproductive status, Natural Increase (NI), Net Replacement Rate (NRR), and Output, of Brahman Cross cattle in Maju Sejahtera Cooperative, Tanjung Sari District, South Lampung Regency. This research was conducted in one month, started from December 2019 to January 2020. Data was collected from all Brahman Cross cattle breeders in the Maju Sejahtera Cooperative by interviewing respondents. Female cattle are used natural mating methods. The age of first mating of heifers is two years. Calving interval (CI) of Brahman Cross cattle at Maju Sejahtera Cooperative is 12.4months. Natural Increase (NI) of Brahman Cross cattle in Maju Sejahtera Cooperative is 29.48%. The Net Replacement Rate (NRR) value of male Brahman Cross cattle at the Maju Sejahtera Cooperative is more than 100% (670.4%). The output of Brahman Cross cattle at the Maju Sejahtera Cooperative is 52.43%.